Living Law-Based Legal Through Harmonizing Customary ‎Justice and the Indonesian Criminal Code: Evidence ‎Education From Kasepekang Sanctions In Bali - Wati, Briliyan Erna (JPI: Jurnal Pustaka Indonesia, 2025)
The recognition of living law under Article 2 of the Indonesian Criminal Code marks a significant shift toward legal pluralism in Indonesia's criminal justice system. This study aims to analyze the implications of recognizing living law for the development of legal education in Indonesia. Using a normative legal research approach with a literature-based design, the study examines primary, secondary, and tertiary legal materials collected through systematic database searches and analyzed using thematic analysis. The findings indicate that, first, Article 2 establishes a conditional framework that accommodates customary law within the national criminal law system while maintaining consistency with the principle of legality. Second, analysis of the Kasepekang customary sanction in Bali demonstrates that tensions between state law and customary law do not arise from an inherent incompatibility between the two systems, but rather from the absence of implementation mechanisms that ensure proportionality, due process, and human rights protection in accordance with Pancasila and the 1945 Constitution. Third, effective implementation of the new Criminal Code requires law enforcement officials to adopt intercultural competence, contextual legal reasoning, and restorative justice approaches to strengthen legal legitimacy and protect indigenous communities. Based on these findings, this study proposes the Practice-Oriented Living Law-Based Legal Education Model (PHBLL), which integrates legal pluralism, interdisciplinary learning, cultural competence, restorative justice, indigenous legal studies, and experiential learning into legal education. The study concludes that the successful implementation of Article 2 depends not only on regulatory reform but also on transforming legal education to prepare future legal professionals capable of reconciling state law and living law within Indonesia's plural legal system.